Human Resource Strategy on Organizational Performance - Ratnasari, Wahyu (Manager : Jurnal Ilmu Manajemen, 2024)
This research aims to explore the impact of human resource (HR) strategies on organizational performance at universities in Balikpapan. Utilizing a qualitative approach, data was gathered from 12 universities to examine how HR practices influence teaching quality, research, services, and institutional competitiveness. The findings indicate that universities with rigorous recruitment and selection processes tend to have more qualified staff, enhancing the quality of education and services. Regular training and development programs lead to increased competency and productivity among employees, fostering innovation and adaptability. Comprehensive performance management systems, including feedback and rewards, boost employee motivation and accountability, further improving institutional outputs. Competitive compensation and benefits packages attract and retain high-quality staff, resulting in greater employee satisfaction and loyalty. Lastly, a positive organizational culture and high employee engagement correlate with increased job satisfaction, productivity, and innovation. Overall, effective HR strategies are crucial for enhancing the performance and competitiveness of universities in Balikpapan.